Properties of compress stabilised laterite interlocking block using recycled fine aggregate - Hasbullah Ali, Abd Rahim (2014)
Construction waste is becoming a serious environmental problem in many large cities in the world including Malaysia. Thus, the minimisation of construction wastes has become a pressing issue. Compressed earth interlocking block (CEIB) is a part of Block Work Systems in Industrialised Building Systems (IBS). Using the CEIB will reduce the construction time and cost in houses construction as it does not required mortal in bricklaying work. The aim of this study is to determine the suitable curing method and to determine the characteristic of the interlocking block using recycled fine aggregate in terms of compressive strength, durability and water absorption. The different percentages of natural fine aggregate and recycled fine aggregate were used in producing the interlocking block (50:50%, and 33.33:66.67%). The curing sets experimental have 4 different type of curing method. The results from the curing sets experimental shows that Set 3# give the highest compressive strength value (7.01 MPa) for 7 days of curing. The curing method of Set 3# will be used in the recycled set experimental. The test result for the interlocking block using recycled fine aggregate show a lower value of compressive strength than interlocking block in curing set 3# (3.78 MPa from interlocking block with 50% replacement of recycled fine aggregate) with 13.33% of water absorption percentage.